Young people of the future. Militancy and Young sociability in the ocuppations of the high schools. Rosario, 1973 (Quinto Sol, 2024)
This article analyzes the occupation of secondary schools in Rosario (Santa Fe, Argentina) during the year 1973 in order to identify the characteristics of this process. It is argued that the occupations were not similar in their composition and development, however, they allowed the gestation of a broad student movement that articulated central demands between 1973 and 1975. It is also argued that they were in parallel and converged at a time of expansion of political militancy of secondary students. It is also maintained that it is possible to analyze the occupation of educational institutions in a generational key where the politicization of young people was articulated with new forms of youth sociability. In this line, the article recovers various experiences that enable us to redefine the young universe in the early seventies.
Keywords: student movements; political participation; school; youth